The Design of Reference Service System in Cordova-based Hybrid Frameworks - Dengke Xin; Lei Zhang*; Xiaoliang Yang; Yuan Fang (Tehnički Vjesnik, 2021)
With the rise of mobile technology, the library reference service has dramatically changed. Targeting the new requirements, this paper aims to design a new library reference service system in Cordova-based hybrid frameworks, which caters to the web service embedded in two major mobile platforms, iOS and Android, as well as the PC platform. The new system adopts the WebSocket based technology to realize the function of independent online reference, which improves the quality of the normal digital reference service. The newly designed system also applies the ECS cloud server technology, thereby significantly slashing the hardware setup cost, extending the basic reference service, and improving its fitness-for-use and convenience, and optimizing the allocation of local resources.